Mandible bone density in adolescents with cerebral palsy using antiepileptic drugs - Pavanello, Andrea; David, Antonio Francisco; Ferreira Costa, Andre Luiz; Botti Rodrigues Santos, Maria Teresa (Brazilian Dental Science, 2022)
Objective: The aim of this study was to assess the bone density of the mandible in adolescents with cerebral palsy (CP) treated with antiepileptic drugs using one beam computed tomography (CBCT). Methods: The study was carried out with 18 adolescents aged 12–18 years, undergoing routine dental treatment at the dental clinic of APCD-São Caetano do Sul. CBCT scans were of divided into two groups: G1 adolescents with CP using antiepileptic drugs and G2 normoactive adolescents. A single dentomaxillofacial radiologist assessed and evaluated the images using Dental Slice software and Image J. Fisher’s exact tests as well as paired and unpaired Student’s t-tests were performed. Results: Groups differed significantly with regard in the values of density (p < 0.001), with G1 presenting lower values compare to G2. G1 showed significantly lower density means on the right side, left side, and right/left sides of the mandible edge than G2 (p < 0.001). Conclusion: CP patients using antiepileptic drugs show evidence of bone mineral density loss of the mandible. KEYWORDS Antiepileptic drugs; Bone mineral density; Cone beam computed tomography; Mandibular indices; Osteoporosis.